ANALISIS KESULITAN MEMBACA PERMULAAN SISWA KELAS II DI SEKOLAH DASAR - Ibrahim, Baldam; Anwar, Aang Solahudin; DS, Yulistina Nur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to describe the analysis of the difficulties of beginning reading of grade II students at SDN Panyingkiran II. This research uses a qualitative approach with a case study type of research. Data was obtained from the class teacher and grade II students of SDN Panyingkiran II. The data collection techniques used in this study were observation, interviews, and documentation. The data obtained was analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results showed that of the 4 grade II students of SDN Panyingkiran II, it was found that RP, SM, AN, and MP had problems in beginning reading. The problems experienced, namely: not yet able to recognize letters, distinguish letters, spell words, and assemble words into sentences.